Anti-osteoporotic effects of Yi Mai Jian on bone metabolism of ovariectomized rats - Bin Shi; Che-Chun Lin; Chia-Jung Lee; Chia-Jung Lee; Chia-Jung Lee; De-Shan Ning; Chao-Chi Lin; Hong-Wei Zhao; Chang-Syun Yang; Shun-Xin Deng; Yung-Jia Chiu; Ching-Chiung Wang; et al. (Frontiers Media S.A., 2024)
Yi Mai Jian herbal formula (YMJ) is formulated with Eucommiae Folium, Astragali Radix, Ligustri Lucidi Fructus, and Elaeagnus Fructus to improve bone function in traditional Chinese medicine. The anti-osteoporotic effects of YMJ in bone metabolism were evaluated in ovariectomized (OVX) rats. The skeletal structure of the femur and vertebrae was analyzed after treating OVX rats with YMJ for 114 days. The results showed that YMJ significantly increased the bone mineral density (BMD) and trabecular number (Tb. N) of the femur and 5th lumbar vertebrae and reduced trabecular separation (Tb. Sp). Moreover, trabecular bone volume/total tissue volume (BV/TV), bone stiffness, and maximum femur load were significantly increased. The serum concentrations of NTX1 and PYD were significantly decreased. According to these results, YMJ could ameliorate osteoporosis in ovariectomized rats. Eucommiae Folium and Elaeagnus Fructus inhibited osteoclast differentiation, Ligustri Lucidi Fructus inhibited calcium reabsorption, Astragali Radix stimulated osteoblast proliferation, and Astragali Radix and Eucommiae Folium stimulated mineralization. Therefore, the combination of the four herbs into one formula, YMJ, could alleviate bone remodeling caused by low estrogen levels. We suggest that YMJ could be a healthy food candidate for preventing post-menopausal osteoporosis.